Assessment of a colposcopic scoring system (Swedescore) to reduce the number of cervical biopsies: a protocol for a clinical multicentre non-randomised intervention study in Denmark - Ulrik Schiøler Kesmodel; Ameli Tropé; Anne Hammer; Pekka Nieminen; Björn Strander; Berit Booth; Ane-Kersti Skaarup Knudsen; Tina Hovgaard Randrup; Line Gustafson (BMJ Open)
Introduction Colposcopy is a standard procedure for evaluating cervical abnormalities and collecting cervical biopsies. The procedure is associated with intra- and inter-observer variation. A colposcopic scoring system, Swedescore, has been designed to standardise and facilitate colposcopy training. Swedescore has performed well in a routine clinical setting when used by expert colposcopists to find or exclude high-grade lesions. Danish clinical guidelines for colposcopy differ from other countries, as they recommend collecting four cervical biopsies in all women regardless of risk factors or colposcopy findings. Swedescore has never been examined to assess the reduction of cervical biopsies in a real-world clinical setting. This study aims to investigate whether the implementation of Swedescore can optimise the diagnostic work-up for whom the collection of biopsies can be safely omitted or reduced.Methods and analysis The design is a clinical multicentre non-randomised intervention study in Denmark. According to a power calculation, we will need to include 586 women referred for colposcopy. Colposcopy with Swedescore will be compared with conventional colposcopy with no Swedescore. Cervical biopsies will be divided into two separate vials (target and random biopsies). The primary outcome will be normal or cervical intraepithelial neoplasia grade 1 detected in cervical biopsies. χ2 and logistic regression will be used to compare estimates between arms.Ethics and dissemination The study protocol has been submitted to the Ethical Committee in Central Denmark region and is not notifiable to the Committee (j.no.: 1-10-72-124-22). Results will be published in a peer-reviewed journal and presented at scientific meetings.Trial registration number NCT05870787.Protocol version Version 3 (date 12. November 2024).